1995
DOI: 10.1007/bf03000201
|View full text |Cite
|
Sign up to set email alerts
|

Selective immunoneutralization of luteinizing hormone results in the apoptotic cell death of pachytene spermatocytes and spermatids in the rat testis

Abstract: The selective withdrawal of pituitary gonadotropins through specific antibodies is known to cause disruption of spermatogenesis. The cellular mechanism responsible for the degenerative changes under isolated effect of luteinizing hormone (LH) deprivation is not clear. Using antibodies specific to LH we have investigated the effect of immunoneutralization of LH on apoptotic cell death in the testicular cells of the immature and the adult rats. Specific neutralization of LH resulted in apoptotic cell death of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
30
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 22 publications
6
30
0
1
Order By: Relevance
“…The output of spermatozoa is determined largely by the shifts in degeneration vs survival of dividing and developing germ cells (Bartke 1995). The survival of spermatogenic cells is dependent on gonadotropins as well as on intratesticular androgens induced by LH (Tapanainen et al 1993, Troiano et al 1994, Billig et al 1995, Marathe et al 1995. Testosterone plays an essential role in preventing apoptotic cell death in androgen-dependent tissues (reviewed in Tenniswood et al 1992, Thompson 1994.…”
Section: Discussionmentioning
confidence: 99%
“…The output of spermatozoa is determined largely by the shifts in degeneration vs survival of dividing and developing germ cells (Bartke 1995). The survival of spermatogenic cells is dependent on gonadotropins as well as on intratesticular androgens induced by LH (Tapanainen et al 1993, Troiano et al 1994, Billig et al 1995, Marathe et al 1995. Testosterone plays an essential role in preventing apoptotic cell death in androgen-dependent tissues (reviewed in Tenniswood et al 1992, Thompson 1994.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported the regulation of both the intrinsic and extrinsic pathway components, Bcl2l2, Casp8, and Casp9, in hpg mice at 13 dpp; however, the specific contribution of testosterone to this process is not known (Chausiaux et al 2008). In adults, several studies have shown that testosterone withdrawal from rat testis leads to an increase in meiotic and spermatogenic cell apoptosis in a stage-dependent manner, and suggested that testosterone may act as a survival factor (Billig et al 1995, HenriksĂ©n et al 1995, Marathe et al 1995, Bakalska et al 2004. Few studies have investigated the molecular mechanism by which testosterone affects germ cell apoptosis in rodents.…”
Section: Germ Cellsmentioning
confidence: 99%
“…In immature rats, testosterone is an absolute requirement for the completion of the first wave of spermatogenesis during puberty (Cameron et al 1993, Marathe et al 1995. Similarly, AR Sertoli cell knockout mice have also displayed arrest at late spermatocytes and beyond (Chang et al 2004, De Gendt et al 2004, suggesting that the completion of meiosis and spermiogenesis is dependent on androgen action in the first wave.…”
Section: Germ Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, what would seem to be a relatively simple question to answer has remained unclear. The elucidation of the role of each hormone in vivo requires perturbation of the system by a variety of experimental conditions: hypophysectomy (Ahmad et al 1975, Russell et al 1987, treatment with a gonadotropin-releasing hormone (GnRH) antagonist (Sinha Hikim & Swerdloff 1993, Billig et al 1995, immunoneutralization of gonadotropin (Marathe et al 1995, Shetty et al 1996 or GnRH (McLachlan et al 1995), treatment with ethane dimethanesulfonate, a cytotoxic compound for Leydig cells (Henriksen et al 1995) or steroid implants (McLachlan et al 1994), or use of specific animal models such as the hypogonadal mouse (O'Shaughnessy et al 1992) or mice rendered deficient in FSH (Kumar et al 1997) or FSH receptor (Dierich et al 1998) by knockout (KO) strategies. However, it has become clear that it is difficult in vivo to perturb testosterone production independently of gonadotropin secretion and reciprocally (Sinha Hikim & Swerdloff 1993, McLachlan et al 1994.…”
Section: Introductionmentioning
confidence: 99%